Repair strategies to breakdowns in everyday interaction by Malay children with repaired cleft - Saad, Mohammad Azannee; Mohd Jan, Jariah (2017)
Repair to conversational breakdowns is important so that mutual understanding between speakers can be restored. Strategies to repair may include but not limited to repetition of trouble source, addition or deletion. However, repair work requires speakers to be equipped with necessary linguistic and cognitive skills (Cho &Larke, 2011) which may be problematic for children with certain disabilities. This study aims to examine how children with such background repair conversational breakdowns that occur during interactions with their parents. Recorded data of interactions within three Malay families, consisting of parents and their children with repaired cleft lip and/or palate, serve as the primary data source. The interactions were recorded during a period of between 14 to 21 months and transcribed using Jefferson’s Transcription Convention (2004). The occurrences of repair strategies were coded and then analysed using Philip’s Repair Initiation Strategies (2008). Results generally show that children with repaired cleft lip and/or palate mostly use open-class repair initiation strategies such as “huh?” which is known to be a weak repair initiator because of their inability to localise the type of trouble source that precedes a turn. Further, “inappropriate” strategy, which is often used, resulted in breakdown sequence thus making repair work a time consuming process. The implications of the study will also be presented.